(3QSGdI aj GdfMhs - (3jhSa GdWQWhTj , jhSa Hf Ydj,J (B740 (3g` s
(3ChdgG (B:s
(3bGd GdaGOGQi CMSf eGbjd Cf jbhd ai MO GdGSe cd daX Od Ydi eYfi ai faSg ZjQ ebJQf HReGf HGH GdEeGdI s
(3BNQgG (B:s
(3hPcQ Cfge CeGdhG CTjGA Ydi ZjQ GdbjGS fMh bhdge LGfi fGS hGdYLGL hGdMLGL hgPG EfeG LGR dcKQI GdGSJYeGd gPG BNQ GdHGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B318s
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(1511) s
Keywords: (3GdfMhs